2014
DOI: 10.1007/s10311-014-0452-8
|View full text |Cite
|
Sign up to set email alerts
|

Tetrabromobisphenol A recovery from computer housing plastic by a new solvothermal process

Abstract: Brominated flame retardants contained in electrical and electronic waste plastic are toxic to both humans and the environment. Most disposal technologies for brominated flame retardants are environmentally unfriendly. Here, a novel solvothermal process was designed to recover tetrabromobisphenol A, a typical brominated flame retardant, from waste computer housing plastic. The plastic waste was treated by the solvothermal process followed by vacuum rotary evaporation. Results show a tetrabromobisphenol A recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…139,140 Recently, the process has been employed for the treatment of plastics as an alternative to inefficient and unsustainable practices such as incineration and landfilling. 141 Karmore and Madras 142 examined the supercritical degradation and kinetics of PS using benzene in a 450 cm 3 high-pressure stirred batch reactor by varying the temperature from 300 to 330 C and fixed pressure of 5 MPa. The results showed that the supercritical conditions significantly improved the degradation rates as evident in the degradation rate coefficients and activation energies, which are two times higher than values reported at similar temperatures and pressures for subcritical solvents.…”
Section: Solvent/solvothermal Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…139,140 Recently, the process has been employed for the treatment of plastics as an alternative to inefficient and unsustainable practices such as incineration and landfilling. 141 Karmore and Madras 142 examined the supercritical degradation and kinetics of PS using benzene in a 450 cm 3 high-pressure stirred batch reactor by varying the temperature from 300 to 330 C and fixed pressure of 5 MPa. The results showed that the supercritical conditions significantly improved the degradation rates as evident in the degradation rate coefficients and activation energies, which are two times higher than values reported at similar temperatures and pressures for subcritical solvents.…”
Section: Solvent/solvothermal Treatmentmentioning
confidence: 99%
“…The results showed that the supercritical conditions significantly improved the degradation rates as evident in the degradation rate coefficients and activation energies, which are two times higher than values reported at similar temperatures and pressures for subcritical solvents. Other studies have also examined the recovery and removal of harmful compounds and substances from plastics through solvothermal treatment 132,141 as a substitute to conventional processes, such as Soxhlet, supercritical fluid, pressurized liquid, and microwave-assisted extraction. The most notable toxic, recalcitrant and bio-accumulative pollutants in plastic wastes are tetrabromobisphenol A (TBBPA), PBDE, and hexabromocyclododecane (HBCDD), which are broadly classified as brominated flame retardants (BFRs), whereas triphenyl phosphate (TPPO) is a organophosphorus flame retardant (PFR).…”
Section: Solvent/solvothermal Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Packaging is used to preserve food quality and provide hygiene safety for the consumer (Zhang et al 2014;Wang et al 2019;Gaikwad et al 2019). It helps in the handling, transportation, and storage by protecting food products from physical (crushing, abrasions, and shocks), chemical (ultraviolet radiations), and biological (microorganism) damage (Al-Tayyar et al 2020a;Youssef et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Toxic liquids and residues of landfills leak contaminate the groundwater. Over the past few decades, recycling and re‐utilization of waste plastics attract more attention because it avoids their accumulation in landfills …”
Section: Introductionmentioning
confidence: 99%